Phase Coherence Technology of Digital MR Console Based on Dual Reference Sources - Wen-shan LIAO; Jun-cheng XU; Shou-quan YAO; Jian-qi LI; Yu JIANG (Chinese Journal of Magnetic Resonance, 2022)
In this article, an effective method to keep the phase coherence between the transmitter and the receiver in digital magnetic resonance (MR) console is proposed. Relying on programmable digital logic, we design two digital reference sources with the same frequency and embed them in the transmitter and the receiver respectively. During pulse sequence execution, when the transmitter or receiver loses phase coherence due to frequency switching, the phase coherence is restored by resetting the phase of the transmitter and receiver to ensure they are synchronized with their corresponding reference source. The experimental results have verified that this method can accurately keep the phase coherence between the transmitter and receiver, and neither additional hardware circuit nor complex sequence design is required, which adds to great practicability.